Characterization of a multi-tolerant tannin acyl hydrolase II from Aspergillus carbonarius produced under solid-state fermentation - Valera, Larissa Serrani [UNESP]; Jorge, Joao Atilio; Souza Guimaraes, Luis Henrique (Univ Catolica De Valparaiso, 2015)
Background: Tannases are enzymes with biotechnological potential produced mainly by microorganisms as filamentous fungi. In this context, the production and characterization of a multi-tolerant tannase from Aspergillus carbonarius is described. Results: The filamentous fungus A. carbonarius produced high levels of tannase when cultivated under solid-state fermentation using green tea leaves as substrate/carbon source and tapwater at a 1:1 ratio as the moisture agent for 72 h at 30 degrees C. Two tannase activity peakswere obtained during the purification step using DEAE-Cellulose. The second peak (peak II) was purified 11-fold with 14% recovery from a Sepharose CL-6B chromatographic column. The tannase from peak II (tannase II) was characterized as a heterodimeric glycoprotein of 134.89 kDa, estimated through gel filtration, with subunits of 65 kDa and 100 kDa, estimated through SDS-PAGE, and 48% carbohydrate content. The optimal temperature and pH for tannase II activity was 60 degrees C and 5.0, respectively. The enzyme was fully stable at temperatures ranging from 20-60 degrees C for 120 min, and the half-life (T1/2) at 75 degrees C was 62 min. The activation energy was 28.93 kJ/mol. After incubation at pH 5.0 for 60 min, 75% of the enzyme activity was maintained. However, enzyme activity was increased in the presence of AgNO3 and it was tolerant to solvents and detergents. Tannase II exhibited a better affinity for methyl gallate (Km = 1.42 mM) rather than for tannic acid (Km = 2.2 mM). Conclusion: A. carbonarius tannase presented interesting properties as, for example, multi-tolerance, which highlight its potential for future application. (C) 2015 Pontificia Universidad Catolica de Valparaiso. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Aspergillus; Microbial enzymes; Solid-state fermentation; Tannase; Tannic acid